A case for monitoring fungi of clinical relevance at beaches: enterococci measures do not correlate with all disease risks - Larissa Montás-Bravo; Helena M. Solo-Gabriele; Débora F. Gil; Ayaaz Amirali; Sebastian P. Arenas; Sofia Hoffman; Adriana Jimenez; Alexandre Mendonça; Rivka Reiner; Raquel Sabino; Konstantina Sarioglou; Mark E. Sharkey; et al. (Environmental Monitoring and Assessment, 2026)
Fungal disease is on the rise, coupled with fungal pathogens increasing in geographic range. Studies have shown that viable fungal pathogens may be present in beach sand and water, and consequently, efforts are ongoing in Europe to develop guidelines for fungi levels at beaches. In the USA, fungal diseases are a growing concern, and yet, they are not subject to public health reporting, and beach environments are currently not routinely monitored for fungal pathogens. This study measured fungal and enterococci levels at two beaches within a subtropical environment in Miami, FL. Samples were analyzed by culture-based methods, with fungi species confirmation by targeted PCR and sequencing. A unique aspect of this study is the analysis with higher incubation temperatures (37 °C and 40 °C) to isolate mesophilic fungi that can cause invasive infections. Results show that levels of fungi were strongly influenced by sample matrix (sand or water). The most common fungal species observed belonged to the Aspergillus and Candida genera, with the isolation of 25 taxa with reports of causing infections, of which 20 were previously reported to exhibit resistance to some or all classes of antifungals available. Results emphasize the need for fungal specific analyses to better understand beach-related disease risks. Given the current increase in cases of fungal diseases and the presence of viable fungi in the environment, integrating fungal measurements in routine microbiological monitoring programs is critical for assessing the beach transmission of pathogenic fungal disease and the control of emerging fungal pathogens.

Impact of new octagonal front-of-pack labeling on purchasing probability of processed and ultra-processed foods in Colombia - Henry Sebastian Rangel-Quinonez; Riccardo Vecchio; Luisa Fernanda Arenas-Estevez (Food Quality and Preference, 2025)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Detection of the clinically persistent, pathogenic yeast spp. Candida auris from hospital and municipal wastewater in Miami-Dade County, Florida - Kristina Babler; Mark Sharkey; Sebastian Arenas; Ayaaz Amirali; Cynthia Beaver; Samuel Comerford; Kenneth Goodman; George Grills; Michelle Holung; Erin Kobetz; Jennifer Laine; Walter Lamar; et al. (Science of The Total Environment, 2023)

A Review on Current Trends in Biogas Production from Microalgae Biomass and Microalgae Waste by Anaerobic Digestion and Co-digestion - Laura Vargas-Estrada; Adriana Longoria; Emilio Arenas; Joel Moreira; Patrick U. Okoye; Yaneth Bustos-Terrones; P. J. Sebastian (BioEnergy Research, 2022)